Resilience of Tamil Hindu Culture through Adhi Thiruvila Ritual in Medan - Matha Riswan (International Journal of Interreligious and Intercultural Studies, 2025)
The aims of this research are to analyze the factors and implications of the resilience of Tamil Hindu culture through Adhi Thiruvila Ritual on the social, cultural and religious life of the Tamil community in Medan. The research results are implementation Adhi Thiruvila ritual becomes a means for the Tamil community to maintain their cultural identity amidst the dynamics of social change that is occurring. Factors that led to the resilience of Tamil Hindu culture through Adhi Thiruvila ritual in Medan, there are five interrelated factors that form a layered defense system, namely spiritual aspects, ancestral heritage, social factors, cultural identity, and educational media. The process of cultural existence consists of elements of ideology, belief/religion, art and language, which mutually reinforce the preservation of the rituals and socio-cultural foundations of Tamil community. The implications of the resilience Tamil Hindu culture through Adhi Thiruvila Ritual are reflected in the cultural, religious and social life of the community, where this event is accepted as a cultural product and legitimate Hindu ritual practice and continues to be preserved through consistent and adaptive implementation